Serum Endothelial Specific Molecule -1(EMS-1) and Uric Acid Levels in Severe Preeclampsia - Abbas, Sura Adnan; Majeed, Bushra M (Journal of Science in Medicine and Life, 2025)
It is estimated that anywhere from 2% to 8% of all pregnancies are affected by the pregnancy-specific condition known as preeclampsia. Preeclampsia continues to be a prominent cause of maternal and neonatal morbidity and mortality around the world, particularly in poor socioeconomic circumstances and in third-world nations. It is thought that between 3 and 10 percent of all pregnancies are impacted with serious illness, which can have an adverse effect on multiple organ systems. Preeclampsia and the problems that might arise from it are among the major causes of maternal death around the world. The purpose of this research was to investigate the relationship between endocan and uric acid levels in severely preeclamptic women. According to the findings of this study, women who were experiencing severe preeclampsia had higher levels of both serum uric acid and endocan (EMS-1). When it comes to predicting a negative outcome for the pregnancy, the performance of serum endocan seems to fall short.